(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Ponto de Acesso Vol. 7, n. 2 (2013) Link de acesso ao número http://www.portalseer.ufba.br/index.php/revistaici/issue/view/781/showToc